A metabonomic investigation on the biochemical perturbation in post-stroke patients with depressive disorder (PSD) - Ding, Xinghua; Liu, Ruoxu; Li, Wenkai; Ni, Hengjia; Liu, Yong; Wu, Dandan; Yang, Shuguang; Liu, Jing; Xiao, Bo; Liu, Shaojun (Metabolic brain disease, 2016)
A metabonomics study based on GC/MS and multivariate statistical analysis was performed involving 28 post stroke depressed (PSD) patients, 27 post-stroke non-depressed (PSND) patients and 33 healthy subjects to investigate the biochemical perturbation in their plasma samples. The outcome of this study showed that there was distinctive metabolic profile for PSD patients. Seven sentinel metabolites showed marked perturbations in PSD patients' blood. The introduction of metabonomics approach may provide a novel metabonomic insight about PSD and the sentinel metabolites for classifying PSD.